AN ANALYSIS OF ILLOCUTIONARY ACTS IN VLADIMIR PUTIN’S ELECTION VICTORY SPEECH - Sabtiana, Rela; Siregar, Otto V. (University of Muhammadiyah Malang, 2024)
Illocutionary acts are a key category of speech acts, frequently analyzed in pragmatic studies to investigate the conveyed meaning of a speaker’s words. These acts are particularly intriguing because of their significant impact on the interpretation of utterances. This study aims to conduct an in-depth examination of the various classifications of illocutionary acts employed in spoken discourse, focusing on a speech delivered by a world leader. Specifically, the analysis draws on Vladimir Putin’s 2024 election victory speech, meticulously studied through qualitative analytical methods. The research employed Searle’s framework to categorize and interpret the speech’s illocutionary acts. The analysis identifies five distinct classifications: assertive (or representatives), commissive, expressive, directive, and declarative. The findings highlight a dominance of assertive/representatives with 20 instances, followed by expressive acts with 10 instances, commissive acts with 5 instances, and a single instance, each of directives and declaratives. This comprehensive analysis sheds light on the intricate linguistic strategies employed in the speech, demonstrating how illocutionary acts contribute to meaning-making and rhetorical effectiveness. The study offers insightful information about how these activities are applied in contemporary political discourse, enriching our understanding of the interplay between language, intent, and influence.